(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines the linguodidactic principles of teaching Russian as a native and non-native language (in a multi-ethnic educational environment). Key concepts of linguodidactics and their connections to pedagogy, psychology, and linguistics are analyzed. The research methods are described: a theoretical analysis of scientific and methodological literature and a systematization of didactic principles applicable to the Russian language. As a result, the levels of the linguodidactic system are identified (target, content, process, and evaluative-result). Conclusions are drawn regarding the need to integrate communicative, cognitive, and cultural approaches.